ANALISIS PERTANGGUNGJAWABAN SYAHBANDAR DALAM KESELAMATAN PELAYARAN DI TINJAU DARI UNDANG-UNDANG NO 17 TAHUN 2008 TENTANG PELAYARAN DI WILAYAH INDONESIA - Kirana, Yanti; Basyarudin, (The Juris, 2020)
Indonesia is the largest archipelagic country in the world which is located on the equator and is located between the continents of Asia and Australia and between the Pacific Ocean and Indian Ocean, therefore it is called the Archipelago In an archipelago, sea transportation should be excellent, because there are islands that can only be connected. by sea transportation. However, in practice in Indonesia, sea transportation has not been managed optimally. Various international provisions have been ratified and even the national provisions are complete, however the implementation of these provisions is still limited to business interests and ignores aspects of shipping security and safety. Before sailing, the harbormaster officer should check, not just receive a report, before giving a sailing lyric, the harbormaster has a very vital role in realizing safety during the voyage, so he must seriously carry out his duties. Human errors often occur due to weak law enforcement. Legal sanctions that are very strict but are not implemented consequently, in other words the sentences imposed do not cause a deterrent effect so that accidents at sea often occur. The research method used in this research is normative juridical research, because this research originates from positive law by looking at its relationship in the application in society, then the data obtained is analyzed qualitatively. Normative qualitative, namely data obtained after being systematically compiled and then analyzed qualitatively and normatively in the form of descriptions, so that conclusions can be drawn to achieve clarity regarding the problems to be examined in this journal.